Pengaruh Kualitas Produk dan Tata Letak Produksi terhadap Produktivitas : Studi Kasus pada Produksi Asin Jambal Roti di Pangandaran - Rina Julianti; Suci Putri Lestari; Ari Arisman (CV. Ulil Albab Corp, 2022)
The purpose of this study was determining the effect of product quality and production layout on Productivity (Case Studi of Asin Jambal Roti Production in Pangandaran). The method was used in this study is a quantitative method, with a research sample of 62 respondents who are workers or employees. The analytical tool was used in this research is multiple linear regression. The results showed that simultaneously Product Quality and Production Layout had a significant effect on Productivity. Partially, Product Quality has a positive and significant effect on Productivity. Partially Production Layout has a positive and significant effect on Productivity